KONSTRUKSI MAQASHID SYARI’AH PROGRESIF: DARI MAQASHID EKSLUSIF MENUJU INSKLUSIF - Nawawi Nawawi; Wawan Juandi (LP2M Universitas Ibrahimy, 2020)
This paper found that the classical Maqashid Syari'ah which had been constructed by the previous ulama was exclusive because it had the main characteristics, namely: the object of study was only fiqh (fiqh oriented), using a partial Madinah periodization, the concept was ambiguous, non-linear, and partly the application is not hierarchically consistent. Consequently, the Maqashid in the current context is less accommodating. Thus, construction is needed the Maqashid Syari'ah moderate, namely: progressive Maqashid Syari'ah . The characteristics, at-tasamuh (maintaining tolerance), comprehensive studies (including theology, fiqh, and Sufism), proposing argumentation kulli from the proposition of juz'i, and use the periodization of Mecca. Besides that, construction Maqashid Syari'ah progressives have two concepts that can develop flexibly. First, the concept janib al-wujud (offensive aspects) can realize universal and inclusive values, such as constitutional, human rights, equality, pluralism, democracy, and the rule of law. Second, janib al-'adam (defensive aspects) can prevent radicalism, terrorism, violence, disintegration, and sectarianism.